A Solution Approach for Two-Stage Stochastic Nonlinear Mixed Integer Programs - Beraldi, Patrizia; Bruni, Maria; Conforti, Domenico (Algorithmic Operations Research, 2009)
This paper addresses the class of nonlinear mixed integer stochastic programming problems. In particular, we consider two-stage problems with nonlinearities both in the objective function and constraints, pure integer first stage and mixed integer second stage variables. We exploit the specific problem structure to develop a global optimization algorithm. The basic idea is to decompose the original problem into smaller manageable optimization subproblems and coordinate their solutions by means of a Branch and Bound approach. Preliminary computational experiments have been carried out on a stochastic version of the Trim Loss problem.